GPU-based high-performance computing for integrated surface–sub-surface flow modeling. (November 2015) - Le, Phong V.V.; Kumar, Praveen; Valocchi, Albert J.; Dang, Hoang-Vu
Abstract: The widespread availability of high-resolution lidar data provides an opportunity to capture micro-topographic control on the partitioning and transport of water for incorporation in coupled surface – sub-surface flow modeling. However, large-scale simulations of integrated flow at the lidar data resolution are computationally expensive due to the density of the computational grid and the iterative nature of the algorithms for solving nonlinearity. Here we present a distributed physically based integrated flow model that couples two-dimensional overland flow and three-dimensional variably saturated sub-surface flow on a GPU-based (Graphic Processing Unit) parallel computing architecture. Alternating Direction Implicit (ADI) scheme modified for GPU structure is used for numerical solutions in both models. Boundary condition switching approach is applied to partition potential water fluxes into actual fluxes for the coupling between surface and sub-surface models. The algorithms are verified using five benchmark problems that have been widely adopted in literature. This is followed by a large-scale simulation using lidar data. We demonstrate that the method is computationally efficient and produces physically consistent solutions. This computational efficiency suggests the feasibility of GPU computing for fully distributed, physics-based hydrologic models over large areas. Highlights: We present an integrated 2-D overland flow and 3-D sub-surface flow model. The model is implemented on a GPU-based parallel computing architecture. Widely adopted benchmark problems for model verification are presented. A large-scale simulation using high-resolution lidar topographic data is presented.